Fuselage metal fatigue in large commercial aircraft. (1st January 2012) - Bibel, G.
Details of a recent aircraft fuselage metal fatigue forensic analysis are presented. Different methods for determining total fatigue cycles are given and compared. The results of this investigation are placed in context with respect to all known catastrophic fatigue failures of commercial aircraft fuselages in the modern era.